Assessment of soil metal distribution and environmental impact of mining in Katanga (Democratic Republic of Congo). (January 2016) - Pourret, Olivier; Lange, Bastien; Bonhoure, Jessica; Colinet, Gilles; Decrée, Sophie; Mahy, Grégory; Séleck, Maxime; Shutcha, Mylor; Faucon, Michel-Pierre
Abstract: Metal and metalloid (As, Cd, Co, Cu, Pb and Zn) distribution in soils from the Katanga Copperbelt (Democratic Republic of Congo) is investigated in order to characterize the environmental impacts of mining and smelting activities in that area. The concentrations of Cu, Co, As, Zn, Pb and Cd in soils from mining sites are higher than in non-metalliferous sites and above permissible metal and metalloid concentrations in soils. Moreover, the fractionation and mobility of Co, and Cu in such environment is assessed using the application of both ammonium acetate-EDTA extraction and speciation modeling (WHAM 6). The resulting data set covers wide range of environmental conditions (pH, trace metals concentration, natural soils and soils affected by mining and ore processing). These extractions show that only a small fraction of Cu and Co is mobile, with variation depending on sites: mobility is higher in soils affected by mining and ore processing. The strong affinity of Mn-oxides for Co may explain lower Co mobility in Mn-rich soils. The high Mn and Fe contents of Cu–Co soils from Katanga may actually exert a protective effect against the toxic effects of Co. Finally, Cu–Co speciation modeling of contaminated sites emphasizes that organic matter strongly sorb Cu whereas Co speciation is mostly by Mn content. This type of study leads to a better understanding of metal fractionation and can guide to define different practices of phytoremediation. Highlights: Higher concentration of Cu and Co in soils from mining site than in barren ones. Only a small fraction of Cu and Co is mobile. Strong affinity of Mn-oxides for Co. Strong affinity of organic matter for Cu.